Meningkatkan Minat pada Mata Pelajaran Matematika Siswa Kelas VI SD Pasirnangka pada Materi Pengelolaan Data - Een Unaenah; Defi Prasasti; Widia Kartika; Sarah As-sikah; Nadia Nurrohmah; Ulia Uswatun Hasana; Fitri Maulida Awalina (RC-INSTITUT, 2020)
The method used in this research is PTK research (classroom action research). In this study, researchers collected data through interviews with grade VI at SD Pasirnangka teachers and collected various existing data sources. From various sources available by analyzing the students in class VI. The purpose of this study was to determine the shortcomings of mathematics in data management materials. Before the researchers conducted the analysis, students' learning ability in Mathematics was still low. This is caused by students' lack of interest in these subjects. Besides, students easily feel bored during the learning process because the teacher only uses the lecture method. So that student activity is less dominant. Based on the results of research that has been carried out, this researcher needs to make corrective actions to improve student learning outcomes in data management materials. Then the learning can be done with discussion groups so that students are more active and understand the subject matter. In the learning process, student activities begin with observation, then ask questions, try, network, and analyze.